Profile of chemical compounds and potency of galangal (Kaempferia galanga L.) essential oils from Kemuning Village, Karanganyar District, Central Java, Indonesia - MUZZAZINAH MUZZAZINAH; AHMAD YUNUS; YUDI RINANTO; YAYAN SUHERLAN; MURNI RAMLI; DWIKA SARNIA PUTRI; DITA WAHYU NINGTYAS; ANNISA LUTHFIA RAHMA; SINDY JIHAN NABILA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Muzzazinah, Yunus A, Rinanto Y, Suherlan Y, Ramli M, Putri DS, Ningtyas DW, Rahma AL, Nabila SJ. 2024. Profile of chemical compounds and potency of galangal (Kaempferia galanga L.) essential oils from Kemuning Village, Karanganyar, Central Java, Indonesia. Biodiversitas 25: 1386-1393. Kencur or galangal (Kaempferia galanga L.) belongs to the Zingiberaceae family, which is known to contain essential oils. K. galanga essential oil is commonly used as a traditional medicine, one of which is to treat inflammation. This study aims to analyze the chemical content of the essential oil of K. galanga from Kemuning Village and their known bioactivities. The material used was essential oil from the distillation of K. galanga rhizome, which is the waste product of Kemuning essential oil production. Gas Chromatography-Mass Spectrometry (GC-MS) was applied to analyze the chemical content of K. galanga essential oil. The results showed that the phytochemical content of K. galanga essential oil compounds were Pentadecane: 36.64%, Cyperene: 1.16%, Alpha-gurjunene: 1.04%, Heptadecane: 1.24%, 8-Heptadecane: 1.68%, Gamma-Muurolene: 1.55%, (2,2)-3,6-Nonadienal: 2.41%, Ethyl (2E), 3-Phenyl-2-Propenoate: 16.02 %, Ethyl P-Methoxycinnamate: 6.36%, and Ethyl P-Methoxycinnamate: 25.54%. This study shows that K. galanga is a good source of phytoconstituents used as industrial raw materials to produce medicines, perfumes, and flavoring ingredients.